2016
DOI: 10.1039/c5dt03796d
|View full text |Cite
|
Sign up to set email alerts
|

Pyridinium–phosphonium dications: highly electrophilic phosphorus-based Lewis acid catalysts

Abstract: Using commercially available 2-pyridyldiphenylphosphine (o-NC5H4)PPh2, a family of electrophilic phosphonium cations [(o-NC5H4)PFPh2](+) (2) and dications [(o-MeNC5H4)PRPh2](2+) (R = F (4); Me (5)) were prepared. The Lewis acidity of these pyridinium-phosphonium dications was probed in Friedel-Crafts dimerization, hydrodefluorination, hydrosilylation, dehydrocoupling and hydrodeoxygenation reactions. The influence of the counterion on the catalytic activity of the electrophilic phosphonium cations is also disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 35 publications
0
19
0
3
Order By: Relevance
“…Therefore, for the purpose of this review we have limited this to catalysis using the s-block elements and the p-block elements which are not typically considered as organocatalysts. There has been a resurgence in main group chemistry in the past decade, with many s-and p-block centered systems acting as efficient catalysts in a vast multitude of reactions such as cyclizations, hydrogenations and annulations amongst many others [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Whilst many of these have been shown to be very effective, routinely obtaining quantitative conversions, any control of enantioselectivity has either been minimal or an incidental by-product.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for the purpose of this review we have limited this to catalysis using the s-block elements and the p-block elements which are not typically considered as organocatalysts. There has been a resurgence in main group chemistry in the past decade, with many s-and p-block centered systems acting as efficient catalysts in a vast multitude of reactions such as cyclizations, hydrogenations and annulations amongst many others [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Whilst many of these have been shown to be very effective, routinely obtaining quantitative conversions, any control of enantioselectivity has either been minimal or an incidental by-product.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these species are effective catalysts in hydrodefluorination, hydrosilylation and hydrodeoxygenation processes , . The remarkable Lewis acidity of these fluorophosphonium compounds is most certainly caused by the presence of electron‐withdrawing perfluoroorganic substituents (here C 6 F 5 ) or cationic imidazolium and pyridinium groups.…”
Section: Introductionmentioning
confidence: 99%
“…Pyridine‐substituted compound 9 and furan‐substituted compound 10 were both formed in good yields, indicating both electron‐rich and electron‐deficient heteroaromatic substituents are compatible (Figure 1). (Note that compound 9 is a precursor to an established phosphonium ion catalyst used for Friedel–Crafts dimerization, hydrodefluorination, and hydrodeoxygenation, among other reactions) [22] . Additionally, we found that alkyl substituents stay intact during deoxygenative fluorination (compound 11 ).…”
Section: Methodsmentioning
confidence: 75%